2015
DOI: 10.1158/1538-7445.am2015-1323
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1323: Both programmed cell death protein 1 and programmed death-ligand 1 molecules can be expressed on the cell surface of small-cell lung cancer

Abstract: Background: Programmed cell death protein-1 (PD-1) and programmed death ligand-1 (PD-L1) play a major role in suppressing the immune system by forming the PD-1/PD-L1 complex, which transmits an inhibitory signal to reduce T-cell activity. PD-L1 is often expressed in various malignant tumors. On the other hand, PD-1 is generally observed in activated lymphocytes and myeloid-derived dendritic cells. Of the malignant cells, only Jurkat cells (under special conditions) and angioimmunoblastic T-cell lymphoma tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…High mutational burden has been reported as a potential predictor of response to immunotherapy ( 8 ). However, despite having one of the highest mutational burdens, small cell lung cancer (SCLC) is often accompanied by relatively high immunosuppression with low levels of T-cell infi ltration and reduced antigen presentation (9)(10)(11). Consistent with this, clinical trials investigating PD-1 or PD-L1 blockade in patients with SCLC have shown low overall response rates ( 12,13 ).…”
Section: Introductionmentioning
confidence: 91%
“…High mutational burden has been reported as a potential predictor of response to immunotherapy ( 8 ). However, despite having one of the highest mutational burdens, small cell lung cancer (SCLC) is often accompanied by relatively high immunosuppression with low levels of T-cell infi ltration and reduced antigen presentation (9)(10)(11). Consistent with this, clinical trials investigating PD-1 or PD-L1 blockade in patients with SCLC have shown low overall response rates ( 12,13 ).…”
Section: Introductionmentioning
confidence: 91%
“…Albeit rare, there are also reports on the promising efficacy of PD-L1 and PD-1 antibodies in SCLC patients, both PD-L1-positive and PD-L1-unselected populations [ 14 15 ]. Both PD-1 and PD-L1 are expressed on the surface of SCLC cells, though the biological implications and the exact functions of PD-1 and PD-L1 in SCLC remain unclear [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 PD-1, PD-L1, and PD-L2 are also overexpressed in various types of tumors, 2 including non-small cell lung cancer (NSCLC). 4,5 This adoption of the PD-1, so-called immune checkpoint, pathway by some tumors enables them to evade surveillance by the immune system, allowing them to grow unchecked. 6,7 The association between tumor PD-L1 expression and prognosis in patients with solid tumors, including NSCLC, has been explored, with findings suggesting a generally negative prognostic effect.…”
mentioning
confidence: 99%